Pelaksanaan Pembelajaran Berdiferensiasi di SMK Negeri 6 Surakarta - Damayanti, Farikha; Tutik Susilowati; Anton Subarno (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
This article aims to investigate the implementation of differentiated learning at SMK Negeri 6 Surakarta. The research focuses on teachers' understanding of the nature and implementation of differentiated learning, as well as the challenges they face in its implementation. To approach this issue, theoretical references are drawn from previous studies relevant to differentiated learning and diverse approaches for students. Data were collected through classroom observations, documentation of teaching materials, and interviews with the head of the curriculum department and teachers who have implemented differentiated learning. The data were then qualitatively analyzed using interactive descriptive techniques. The findings of this study conclude that the majority of teachers have a good understanding of the nature of differentiated learning and recognize the importance of valuing student diversity. However, teachers face several challenges, including managing classes with diverse levels of abilities, limited resources and technology, and differences in understanding and approaches in implementing differentiated learning. Efforts made to overcome these challenges include teacher training and development, the use of technology and digital resources, collaboration among teachers, and a flexible approach to teaching. Thus, this article provides an overview of the implementation of differentiated learning at SMK Negeri 6 Surakarta and recommendations for improving its implementation more effectively.